2006
DOI: 10.1007/s10071-006-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Face processing in humans and new world monkeys: the influence of experiential and ecological factors

Abstract: This study tests whether the face-processing system of humans and a nonhuman primate species share characteristics that would allow for early and quick processing of socially salient stimuli: a sensitivity toward conspecific faces, a sensitivity toward highly practiced face stimuli, and an ability to generalize changes in the face that do not suggest a new identity, such as a face differently oriented. The look rates by adult tamarins and humans toward conspecific and other primate faces were examined to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Human subjects with no chimpanzee expertise have recently been shown to use holistic processing (composite effect) for chimpanzee faces, compared with the faces of more phylogenetically distant species including gorillas [70]. However, there is little evidence beyond these data for any type of configural superiority for human or chimpanzee faces and the basic first-order configuration is similar in all primate faces [32,36,39].…”
Section: Part 1 (A) Configural Information In Facesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human subjects with no chimpanzee expertise have recently been shown to use holistic processing (composite effect) for chimpanzee faces, compared with the faces of more phylogenetically distant species including gorillas [70]. However, there is little evidence beyond these data for any type of configural superiority for human or chimpanzee faces and the basic first-order configuration is similar in all primate faces [32,36,39].…”
Section: Part 1 (A) Configural Information In Facesmentioning
confidence: 99%
“…In addition, similar to previous studies, the majority of the fixations were directed towards the eyes. These free viewing tasks are often used to demonstrate individual recognition, as defined above; however, because the test pair contained one previously viewed photograph and one novel photograph, subjects could simply have responded with increased attention to the novel photograph, not selective attention to the novel individual (see also [36]). …”
Section: Part 2 (A) Individuating Facesmentioning
confidence: 99%
“…Face recognition in nonhuman primates is also characterized by the inversion effect, providing evidence of holistic processing for upright faces ( cotton-top tamarins , Neiworth, Hassett and Sylvester 2007: chimpanzees , Parr et al 1998; Parr and Heintz 2008; Tomonaga 2007; Tomonaga et al 1993: Japanese monkeys , Tomonaga 1994: rhesus monkeys , Dahl et al 2007; Gothard et al 2009; Parr et al 2008; Vermeire and Hamilton 1998). An outstanding question, however, is whether all primates use the same second-order information to recognize faces.…”
mentioning
confidence: 99%
“…cats, snakes), but no such reactions to the videos of non-predator mammals. Using a preference to novelty paradigm, Neworth et al [2004] found categorical representation of pictures by cotton-top tamarins at a level similar to human infants, and Neworth et al [2007] report that tamarins show an experientially driven configural picture processing strategy toward the faces of species with which they have vast experience (tamarins and humans) and a conspecific configural processing toward subtle changes in tamarin faces. Anderson et al [2009] tested video self-recognition in tufted capuchins.…”
Section: Introductionmentioning
confidence: 99%